The financing of development cooperation at the United Nations: why more means less - Timo Casjen Mahn (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
Changes in the financing of United Nations development cooperation (UN-DC) are gradually eroding the multilateral character of UN development aid. Two trends have become clear over the past 15 years. First, donors have more than doubled their financial contributions for UN development cooperation. Second, the character of these contributions has fundamentally changed: while the share of core financing – i.e. funding for the multilateral mandate of the UN's 37 operational agencies – has been shrinking for years, contributions earmarked for specific locations and issues - thus resembling bilateral contributions - have skyrocketed. The balance between the two types of financing is thus shifting, and the result could be a major makeover of the system as a whole. Global development challenges such as climate change require concerted action among nations in today's networked world. Of itself, the UN's universal membership offers a highly appropriate multilateral framework for this purpose and gives its development system a special legitimacy, which also extends to setting norms and standards. But current financing practices are putting pressure on UN development cooperation: more and more, donors are bilaterally earmarking contributions for projects that they prefer, thus profiting from the UN brand without directly contributing to the cost of its multilateral mandate in the form of core contributions. The problem is aggravated when competing UN agencies offer financial incentives which encourage potential donors to expand their bilateralized portfolios. Given that these incentives are subsidized from core budgets, the provision of future core contributions thus becomes less attractive to donors. Complete bilateralisation of the UNDC therefore becomes a plausible scenario if current development trends continue to result in a downward spiral of dwindling core contributions. Clearly, something must change. Unfortunately, individual donors have few incentives to make a fundamental change in their behaviour. One way to prevent a mass movement of donors onto the bandwagon of bilateral earmarking would be a 'codex of good donorship' which should rest on three pillars: a critical mass of core funding with respect to each donor's financial wherewithal; a system-wide obligation of full recovery of costs for programme support and management regarding earmarked projects, with standards for cost classification to be used by the Secretariat for monitoring; and financial commitments for 3-5 years instead of the present practice of annual stop-and-go support for long-term development processes in programme countries. Negotiating such a codex should be one of the first tasks of the newly founded Global Partnership for Effective Development Cooperation, whose steering committee consists not only of traditional donors, but also of emerging powers and UN agencies.
Keywords: 330; Regionale + globale + transnationale Governance; Entwicklungsfinanzierung und öffentliche Finanzen; Governance